Pulsed laser liquid-solid interaction synthesis of Pt, Au, Ag and Cu nanosuspensions and their stability. (24th October 2008) - Maaza, M.; Chambalo, Herculano; Ekambaram, S.; Nemraoui, O.; Ngom, B.D.; Manyala, N.
This paper reports on the stability of Pt, Ag, Au and Cu nanosuspensions synthesised by Laser Liquid-Solid Interaction (LLSI) with the fundamental Nd:YAG frequency. The stability of the metallic nanoparticles in three different dispersing liquid agents, namely, water, acetonitrile and pentane, has been investigated in terms of the solvents' polarisability index, local electric molecular dipole and viscosity. These parameters were varied within the following value range: 0.0-10.2 PI, 0.0-3.44 Debyes and 0.23-1.0 cP, respectively. The stability of the metallic nanoparticles within the dispersing agents was mainly investigated via their respective surface plasmon peaks which occur in UV-VIS spectral range.